PEMBERDAYAAN RUANG LITERASI GUNA MENINGKATKAN MINAT BACA DI TAMAN PENDIDIKAN AL-QUR’AN DESA AIR JOMAN - Muthia Dewi; Dailami Dailami; Nurleni Lubis; Wanda Sekar Lembayung; Asma Najwi Nadila (Smart Education, 2025)
Abstract: This community service activity aims to empower the literacy space at the Air Joman Village Al-Qur'an Education Park to increase reading interest among children and the surrounding community. Targets achieved include the availability of a well-organized literacy space, increased student participation in reading activities, and growing awareness of the importance of literacy culture from an early age. The methods used were needs observation, organizing reading materials, mentoring reading activities, and implementing a creative literacy program with a participatory approach. The results of the activity showed increased enthusiasm in utilizing the literacy space, an increase in the reading collection, and the creation of a more enjoyable and sustainable learning environment. Keywords: Literacy Space, Reading Interest, Al-Qur'an Education Park Abstrak: Kegiatan pengabdian kepada masyarakat ini bertujuan memberdayakan ruang literasi di Taman Pendidikan Al-qur’an Desa Air Joman guna meningkatkan minat baca anak-anak dan masyarakat sekitar. Target yang dicapai meliputi tersedianya ruang literasi yang tertata, meningkatnya partisipasi peserta didik dalam kegiatan membaca, serta tumbuhnya kesadaran pentingnya budaya literasi sejak dini. Metode yang digunakan adalah observasi kebutuhan, penataan bahan bacaan, pendampingan aktivitas membaca, serta penerapan program literasi kreatif dengan pendekatan partisipatif. Hasil kegiatan menunjukkan meningkatnya antusiasme dalam memanfaatkan ruang literasi, bertambahnya koleksi bacaan, serta terciptanya lingkungan belajar yang lebih menyenangkan dan berkelanjutan. Keywords: Ruang Literasi, Minat Baca, Taman Pendidikan AL-Qur’an